EFFICACY OF THERAPEUTIC MEASURES IN ACUTE PURULENT-DESTRUCTIVE LUNG DISEASES IN PATIENTS WHO HAVE HAD SARS-COV-2 - Alisher O. Okhunov (Central Asian Journal of Medicine, 2024)
Background. Since the discovery of SARS-CoV-2, purulent-destructive lung diseases have been increasingly diagnosed around the world in patients who have fallen ill or had COVID-19 pneumonia. The relevance of this pathology is because the pathology is painful for the patient, time-consuming for the doctor and expensive for the medical institution. Material and methods. The results of a comprehensive examination and treatment of 128 patients with acute purulent-destructive lung diseases who had SARS-CoV-2 for the period 2020-2022 are analyzed. Differentiated therapies were used, which were assessed by immediate outcomes. Results. As a result of the use of therapeutic and diagnostic measures developed by us based on the assessment of the degree of endothelial dysfunction in the lungs, it was possible to increase the level of complete recovery from 23.1% to 41.3%, clinical recovery from 35.4% to 44.4%, reduce the frequency of transition of the inflammatory process into a chronic form from 26.2% to 7.9% and, accordingly, the lethal outcome - from 15.4% to 6.3%. Conclusion. The use of the treatment methods developed by us allows us to increase the positive results of treatment, and reduce the frequency of unsatisfactory treatment results and mortality.